Kepemimpinan Spiritual Pesantren dalam Transformasi Digital: Menjaga Otoritas Keagamaan dan Mendorong Inovasi Tata Kelola Pendidikan - Kacung Wahyudi; Abd. Aziz; Lathyva Nur Wahyuni (Islamic Education Management Study Program, Tarbiyah and Teacher Training Faculty, State Islamic University of Madura, 2026)
Digital transformation requires pesantren to preserve religious authority while renewing educational governance without abandoning their values and traditions. This study aims to analyze spiritual leadership at Pondok Pesantren Nurul Islam Karangcempaka, Bluto, Sumenep in maintaining religious authority and directing innovation in educational governance. The research employed a qualitative approach with a case study design. Data were collected through interviews, observations, and documentation, then analyzed through data reduction, data display, and conclusion drawing with source and technique triangulation. The findings show that spiritual leadership serves as the foundation of pesantren management through exemplary conduct, trustworthiness, deliberation, and the cultivation of moral discipline. Digital developments do not weaken religious authority, but instead strengthen the role of the kiai and teachers as the primary references. Digital innovation develops gradually, selectively, and remains aligned with the identity of the pesantren. These findings confirm the importance of spiritual leadership in strengthening adaptive, value-rooted pesantren.